Level of knowledge on preeclampsia following health education through a WhatsApp group - Prihazty, Anggi Wilis; Atika; Wittiarika, Ivon Diah; Ernawati (Universitas Airlangga, 2024)
HIGHLIGHTS WhatsApp groups can effectively overcome the constraints of antenatal care in delivering health education to pregnant women. The scope of health information about pregnancy should be expanded as this study has shown that it enhances their level of knowledge. ABSTRACT Objective: Hypertension in pregnancy, including preeclampsia, is the third most common cause of maternal mortality in Indonesia. One of the problems is low preeclampsia knowledge in the community. WhatsApp, as a social media platform, could facilitate spearheading promotive and preventive efforts, especially for high-risk mothers in the community. This study aimed to analyze the difference in levels of knowledge after receiving education through WhatsApp groups. Materials and Methods: This was a pre-experimental study using one group pre-test and one post-test design. The sample size was 58 high-risk pregnant women in one of the Public Health Centers in Surabaya. Respondents completed a preeclampsia knowledge questionnaire before and after receiving health education via WhatsApp group for 12 days. The results were analyzed using the Wilcoxon signed rank test, Mann-Whitney U-Test, and Kruskal Wallis test. Results: Most respondents had good knowledge about preeclampsia before and improved after intervention. All respondents had a difference in knowledge before and after the intervention (p <0.001). The only factor that showed a difference in the initial knowledge level about preeclampsia was previous exposure to preeclampsia information (p=0.014). Conclusion: Health education through WhatsApp groups can be considered to be provided as it has been proven effective in increasing the knowledge among high-risk pregnant women about preeclampsia.